Electropolymerized Poly(3,4-ethylenedioxythiophene)/Screen-Printed Reduced Graphene Oxide–Chitosan Bilayer Electrodes for Flexible Supercapacitors - Tseng, Chia-Hui (ACS Omega, 2021)
[Image: see text] An electropolymerized poly(3,4-ethylenedioxythiophene) (PEDOT)/screen-printed reduced graphene oxide (rGO)–chitosan (CS) bilayer material was coated on carbon cloth to form electrodes for gel-electrolyte flexible supercapacitors. The conductive polymer and carbon-based materials mainly contribute pseudocapacitance (PC) and electrical double-layer capacitance (EDLC), respectively. The high porosity and hydrophilicity of the PEDOT/rGO–CS bilayer material offers a large contact area and improves the contact quality for the gel electrolyte, thereby enhancing the capacitive performance. Cyclic voltammetry (CV) under a potential scan rate of 2 mV/s revealed that a maximum areal capacitance of 1073.67 mF/cm(2) was achieved. The capacitance contribution ratio PC/EDLC was evaluated to be ∼67/33 by the Trasatti method. A 10,000-cycle CV test showed a capacitance retention rate of 99.3% under a potential scan rate of 200 mV/s, indicating good stability. The areal capacitance remains similar under bending with a bending curvature of up to 1.5 cm(–1).